1985
DOI: 10.1021/ic00201a024
|View full text |Cite
|
Sign up to set email alerts
|

Electron self-exchange in dicyanoiron porphyrins

Abstract: a strong case cannot be made for S,N,0 chelation by cysteine and penicillamine.A substantial contribution of S,N chelation to kinetic Cu(II)-S bond stability is readily apparent from the fc2((Me6tren)Cu-SR, (tmpa)Cu-S-pen) and A:3((tmpa)Cu-S-cys and -S-cme) rate constants. The presence of an optimal, five-membered S,N chelate unit certainly would stabilize the Cu(II) oxidation state and retard Cu(II)-S bond breaking in a reductive-elimination pathway leading to Cu(I) and a monodentate, N-bonded thiyl radical. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

1985
1985
2019
2019

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 5 publications
0
16
0
Order By: Relevance
“…The experimentally determined Fe II/III potential, self-exchange rate constant, and equilibrium and rate constants for the reversible reaction with O2 and are in Table 1. 28,32 The reversible adduct formation between PP-Fe(Im) and O2 have kon = 5.5 x 10 7 M -1 s -1 and koff = 310 s -1 . By determining the associated equilibrium constants for OSET and ISET reactions with O2 (Scheme 5 and Table 1), the MCR can then be used to determine rate constants and compared against experiment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The experimentally determined Fe II/III potential, self-exchange rate constant, and equilibrium and rate constants for the reversible reaction with O2 and are in Table 1. 28,32 The reversible adduct formation between PP-Fe(Im) and O2 have kon = 5.5 x 10 7 M -1 s -1 and koff = 310 s -1 . By determining the associated equilibrium constants for OSET and ISET reactions with O2 (Scheme 5 and Table 1), the MCR can then be used to determine rate constants and compared against experiment.…”
Section: Resultsmentioning
confidence: 99%
“…It is reasonable to estimate a self-exchange rate constant based on literature precedents (e.g., porphyrin ≈ 10 5 -10 7 M -1 s -1 and non-heme ≈ 10 3 -10 4 M -1 s -1 ). 32,36,45 When experimental equilibrium constants for O2 binding are not known, one can use density functional theory to compute an estimated BDFEFe-O2. To demonstrate, a DFT calculation (B3LYP 6-31G*) affords a BDFEFe-O2 of 32 kcal/mol in MeCN (13 kcal/mol in water) for a protoporphyrin IX derivative "PP" (Chart 2; See SI) that is close enough to the experimental value 27 kcal/mol to place a complex on the threshold lines.…”
Section: Implications In Designing Catalysts For Ionic Mechanismsmentioning
confidence: 99%
“…Such an analysis of the solvent influence on the rate constants has previously been successfully applied to a related compound, dicyanoiron porphyrin, in DMSO and methanol. 34 However, in the case of acetone as solvent, there is no direct relation between the solvent parameters and the observed rate constant. At the present stage of investigation, there is no satisfactory explanation for this result.…”
Section: Self-exchange Reactions Of Iron Fluorinated Porphyrinsmentioning
confidence: 99%
“…29 -32 Some measurements have also been performed by Dixon and co-workers using 1 H NMR line broadening analysis. 33 -36 Only one study reported the direct determination of dicyanoiron(II, III)protoporphyrin and deuteroporphyrin self-exchange electron rate constants, 34 (for a recent review, see Ref. 37), one of the limits being the complexity of the natural porphyrin proton spectra.…”
Section: Introductionmentioning
confidence: 99%
“…1. This method is based on selfexchange electron transfer between Fe(II) and Fe(III), which has been used for the determination of the kinetic rate constants [16][17][18][19][20]. Under the assumption that the rate for electron exchange between paramagnetic 1 and diamagnetic 2 is fast on the NMR time scale, the observed 1 H and 13 C NMR chemical shifts(δ obs ) of 2 containing x equiv of 1 can be expressed by Eq.…”
mentioning
confidence: 99%